Aplicación de cocteles microbiano y bovinaza-cascarilla de arroz para la recuperación de muestras de suelos salinos del sitio Correagua, Manabí - Álava Chumo, Diana Gissel (2017)
The objective of this research was to apply microbial cocktails with bovine + rice husks (BC) for the recovery of saline soils in a place called Correagua - Manabí, the initial sample had an Electric Conductivity (EC) of 50.37 dS / m, each experimental unit was constituted in 6 kg of soil distributed in 8 treatments with five replicates each: T1 = (Trichoderma harzianum + 0.5% BC); T2 = T. harzianum + 1% BC; T3 = (Paecilimyces lilacinus, Metarhizium anisopliae Beauveria bassiana + 0.5% BC); T4 = (P. lilacinus, M. anisopliae, B. bassiana + 1% BC); T5 = (Azospirillum brasilense, Azotobacter choococcum, Lactobacillus acidophilus and Saccharomyces cerevisiae + 0.5% BC); T6 = (A. brasilense, A. choococcum, L. acidophilus and S. cerevisiae + BC 1%); T7 = (Combination of all microorganisms (CM) + BC 0.5%); T8 = (CM + 1% BC). The variables studied were pH, EC, Salinity. The obtained data were submitted to the statistical analysis in InfoStat with Duncan significance test with 5% probability, resulting in that the best treatments were T1 (with 79.7% efficiency) and T2 (80.6%), concluding that these alternatives are effective for the recovery of saline soils, but T1 is recommended because of its lower economic cost.